2022
DOI: 10.1038/s41539-022-00135-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of a social-psychological intervention translated from controlled trials to classrooms

Abstract: Social-psychological interventions have raised the learning and performance of students in rigorous efficacy trials. Yet, after they are distributed “in the wild” for students to self-administer, there has been little research following up on their translational effectiveness. We used cutting-edge educational technology to tailor, scale up, and track a previously-validated Strategic Resource Use intervention among 12,065 college students in 14 STEM and Economics classes. Students who self-administered this “Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Another example is the University of Michigan's use of ECoach, an AI-powered personalized adaptive learning (PAL) model that provides students with scaffolded feedback, resources, and study strategies, helping them to navigate their courses more effectively (University of Michigan n.d.). An evaluation of ECoach found that it improved student performance and reduced achievement gaps, which may be relevant to improving outcomes for first-generation students and students from lowerincome backgrounds (Chen et al 2022). Despite the availability of these higher education-specific systems tailored for learners and adaptable to specific courses, publicly available GenAI tools, such as CoPilot, ChatGPT, and Gemini mean that students are also able to access an additional layer of highly flexible and customizable GenAI tools at any time.…”
Section: Current State Of Generative Ai In Higher Educationmentioning
confidence: 99%
“…Another example is the University of Michigan's use of ECoach, an AI-powered personalized adaptive learning (PAL) model that provides students with scaffolded feedback, resources, and study strategies, helping them to navigate their courses more effectively (University of Michigan n.d.). An evaluation of ECoach found that it improved student performance and reduced achievement gaps, which may be relevant to improving outcomes for first-generation students and students from lowerincome backgrounds (Chen et al 2022). Despite the availability of these higher education-specific systems tailored for learners and adaptable to specific courses, publicly available GenAI tools, such as CoPilot, ChatGPT, and Gemini mean that students are also able to access an additional layer of highly flexible and customizable GenAI tools at any time.…”
Section: Current State Of Generative Ai In Higher Educationmentioning
confidence: 99%